THE ASYMPTOTIC FORMULAS FOR THE SUM OF SQUARES OF NEGATIVE EIGENVALUES OF A SINGULAR STURM-LIOUVILLE OPERATOR - Sezer, Yonca (UNIV POLITEHNICA BUCHAREST, SCI BULL, 2017)
In this work, I find the asymptotic formulas for the sum of squares of negative eigenvalues of the operator L which is formed by differential expression l(y) = (p(x)y'( x))' q(x) y(x) in the space L-2 [0, infinity), with the boundary condition y( 0) = 0.
Keywords: Hilbert Space; self-adjoint operator; semi bounded operator; eigenvalue; discrete spectrum; Mathematics; Physics